2014
DOI: 10.1002/hed.23372
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser microsurgery for the unknown primary: Role for lingual tonsillectomy

Abstract: A surgical algorithm for the unknown primary that includes TLM-assisted techniques, including a lingual tonsillectomy, offers the greatest likelihood of successfully detecting the location of occult primary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 34 publications
(95 reference statements)
1
66
1
1
Order By: Relevance
“…The additional diagnostic yield of TOLM and TORS for head and neck CUP has prompted some authors to recommend upfront lingual tonsillectomy at the time of panendoscopy + biopsy, instead of following negative targeted biopsies of the oropharynx [8,29,30]. This has been shown to be a more cost-effective approach from reductions in delays to diagnosis, and the additional expense of a second operation.…”
Section: Diagnostic Transoral Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The additional diagnostic yield of TOLM and TORS for head and neck CUP has prompted some authors to recommend upfront lingual tonsillectomy at the time of panendoscopy + biopsy, instead of following negative targeted biopsies of the oropharynx [8,29,30]. This has been shown to be a more cost-effective approach from reductions in delays to diagnosis, and the additional expense of a second operation.…”
Section: Diagnostic Transoral Surgerymentioning
confidence: 99%
“…TOLM alone has enhanced occult tumour detection rates following lingual tonsillectomy of 61%-68% [8,30] versus 51%-100% for TORS lingual tonsillectomy [28,[31][32][33][34][35][36]. Compared to TOLM lingual tonsillectomy, TORS has the added advantage of superior three-dimensional (3D) high-definition visualisation, wider range of instrument motion with seven degrees of freedom plus the ability to manoeuvre around corners with the help of angled scopes, significant reduction in hand tremors, decreased fatigue, and improved hand-eye coordination [35,37].…”
Section: Tolm Versus Tors Lingual Tonsillectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Transoral laser microsurgery may also be an option for detecting primary tumours in SCCUP patients with comparable detection rates, and can be recommended in Institutes where robotic surgery is unavailable [9,16]. Studies using a TORS approach have found high detection rates (77-90%), but they used different definitions of a true 'SCCUP' syndrome; however, they still managed to identify the majority of primary tumours in the oropharyngeal palatine and lingual tonsils.…”
Section: Discussionmentioning
confidence: 96%
“…Recent case series have reported high rates of detection ranging from 86 to 94% including TLM [38,39] and 72 to 90% including TORS [37,38,40] in the diagnostic work-up of patients with suspected CUP. According to Durmus et al [41] the PT was identified in 77% of patients (17 of 22) with 80% HPV-positive LNM residing in the palatine tonsil in 59% (13 of 22), and the BOT in 18% (4 of 22).…”
Section: Discussionmentioning
confidence: 99%